2013
DOI: 10.1021/jf305182u
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Phenolic Compounds from Iceberg Lettuce and Impact on Enzymatic Browning

Abstract: Enzymatic browning is generally reported as the reaction between phenolic substances and enzymes. The quality of iceberg lettuce is directly linked to this discoloration. In particular, the color change of lettuce stems considerably reduces consumer acceptance and thus decreases sales revenue of iceberg lettuce. Ten phenolic compounds (caffeic acid, chlorogenic acid, phaseolic acid, chicoric acid, isochlorogenic acid, luteolin-7-O-glucuronide, quercetin-3-O-glucuronide, quercetin-3-O-galactoside, quercetin-3-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 33 publications
7
52
1
2
Order By: Relevance
“…Our findings support those previous publications that showed that browning of midribs results from the increased production of caffeic acid derivatives via PAL and their subsequent oxidation and polymerization. This is partially in line with the report of Mai and Glomb (2013) who described that caffeic acid, chlorogenic acid and isochlorogenic acid increased in 24 h-aged sliced iceberg lettuce. In tobacco transgenic leaves, PAL has been shown to be the key control point for flux into chlorogenic acid (Howles et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings support those previous publications that showed that browning of midribs results from the increased production of caffeic acid derivatives via PAL and their subsequent oxidation and polymerization. This is partially in line with the report of Mai and Glomb (2013) who described that caffeic acid, chlorogenic acid and isochlorogenic acid increased in 24 h-aged sliced iceberg lettuce. In tobacco transgenic leaves, PAL has been shown to be the key control point for flux into chlorogenic acid (Howles et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…In the case of cut edge browning, also known as senescence browning, differences in browning development have not been attributed to differences in enzymatic activities, in the quantity of phenolic substrates (Cantos et al, 2001), and/or in endogenous ascorbic acid (AA) content (Heimdal et al, 1995). In fact, the total concentration of phenolic compounds and the activity of PPO in various parts of the lettuce, such as green leaves, yellow leaves, stem and a mix of the entire head, have been reported not to be directly related to the browning process (Mai and Glomb, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of this enzyme in plant tissues does not, however, always correlate with the subsequent development of discolouration in lettuce (Ke and Saltveit 1989;Couture et al 1993;Heimdal et al 1995;Castañer et al 1999;Cantos et al 2001;Mai and Glomb 2013). It is possible that discrepancies between different studies are a reflection of a paradigm which is an oversimplification of the processes involved.…”
Section: Biochemistry Of Oxidative Discolourationmentioning
confidence: 99%
“…8 This was based on literature that described enzymatic browning as the reaction between phenolic substances and enzymes. 4,9,10 Unexpectedly, the total concentration of polyphenols and the activity of PPO were not directly related to the browning processes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Model incubation experiments of plant extract solutions supported the argument that, in addition to the typical enzymatic browning induced by PPOs, further mechanisms must be considered to explain total browning of lettuce. 8 Post-infectious defense induces the formation of antimicrobial substances in plants. The German plant pathologist K. O. Muller established the term "phytoalexin" in 1940.…”
Section: ■ Introductionmentioning
confidence: 99%